Performance analysis of a time-threshold based bandwidth allocation scheme using a one-dimensional markov chain in cellular networks - Candan, Idil; Salamah, Muhammed (My University, 2007)
In this paper, the performance analysis of a time-threshold based bandwidth allocation scheme is presented. The main idea of the scheme is based on monitoring the elapsed real time of handoff calls and according to a time threshold parameter; a handoff call is either prioritized or treated as a new call. The scheme is modeled using a one-dimensional markov chain and numerical results are presented to estimate new call blocking probability, handoff dropping probability and system utilization. The scheme is also simulated under different network conditions. It is observed that the analytical and simulation results agree well. Also in this paper, the different bandwidth allocation schemes are compared using a performance measure (Z). The results indicate that our scheme outperforms other traditional schemes. © 2007 IEEE.
12th IEEE International Symposium on Computers and Communications, ISCC '07 --
Keywords: Analytical model; Bandwidth allocation; Handoff; Markov chain